2016
DOI: 10.1016/j.visres.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining ocular safety with light exposure, focusing on devices for optogenetic stimulation

Abstract: Optogenetics methods are rapidly being developed as therapeutic tools for treating neurological diseases, in particular, retinal degenerative diseases. A critical component of the development is testing the safety of the light stimulation used to activate the optogenetic proteins. While the stimulation needs to be sufficient to produce neural responses in the targeted retinal cell class, it also needs to be below photochemical and photothermal limits known to cause ocular damage. The maximal permissible exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
1
33
0
1
Order By: Relevance
“…We observed that averaged and normalized photocurrent followed a similar photo-sensitivity curve (Fig. 4D), 18 with activation threshold in the 10 15 photons.cm -2 .s -1 intensity range, and robust responses to light stimuli at a wavelength of 600 nm (+/-10 nm) well below the illumination radiation safety limits for the human eye 21,29,30 . When comparing peak photocurrent or peak firing rate for maximal light intensity (3.15 x 10 17 photons.cm -2 .s -1 ), we found no statically significant difference between the two expression durations ( Fig.…”
Section: Subhead 4: Chr-tdt Can Produce High Temporal Photocurrent Anmentioning
confidence: 55%
See 3 more Smart Citations
“…We observed that averaged and normalized photocurrent followed a similar photo-sensitivity curve (Fig. 4D), 18 with activation threshold in the 10 15 photons.cm -2 .s -1 intensity range, and robust responses to light stimuli at a wavelength of 600 nm (+/-10 nm) well below the illumination radiation safety limits for the human eye 21,29,30 . When comparing peak photocurrent or peak firing rate for maximal light intensity (3.15 x 10 17 photons.cm -2 .s -1 ), we found no statically significant difference between the two expression durations ( Fig.…”
Section: Subhead 4: Chr-tdt Can Produce High Temporal Photocurrent Anmentioning
confidence: 55%
“…This was tested under a RGC specific promoter 20 . However, the 5 required blue light intensities were close to radiation safety limits 21 . It was thus clinically important to evaluate other potentials opsins conferring a balance between light sensitivity and channel kinetics 22 .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…First, many of the light-sensitive channels available for optogenetics today are relatively insensitive to ambient light 13 , 14 and thus require additional technology that transforms ambient light from natural scenes to a high-illuminance version to be presented to the retina. 15 – 18 Second, there is a need for an encoding scheme that simulates the natural intraretinal processing in order to make a natural scene intelligible by activation of postreceptoral cells. 10 , 19 Third, eyes with low vision tend to have lost normal oculomotor control 20 – 22 and thus require eye tracking methods to allow presentation of high-luminance encoded patterns to a specific part of the retina reproducibly time after time.…”
mentioning
confidence: 99%